Niemann - Pick C2 regulates steroid hormone secretion and lipid deposition in chicken follicular granulosa cells - Ruihao Yu; Shuo Wei; Felix Kwame Amevor; Liuting Wu; Dan Xu; Zheliang Liu; Kunlong Qi; Yingjie Wang; Gang Shu; Xiaoling Zhao (Poultry Science, 2025)
Follicular development is tightly regulated by the coordinated action of multiple hormones and complex gene regulatory networks in granulosa cells, which play a crucial role in egg production and fertility in hens. Extensive studies have established that Niemann-Pick C2 (NPC2) is a key regulator of cholesterol metabolism and steroid hormone secretion in mammals. However, its specific role in chicken ovarian granulosa cells remains unclear. In this study, cultured chicken ovarian granulosa cells were used to investigate the function of NPC2 through transfection with NPC2 overexpression vectors or small interfering RNAs (siRNAs). The results showed that silencing NPC2 significantly increased the expression of SREBP1, SREBP2, LPL, SCD1, CPT1 and DGAT2 genes involved in lipid synthesis (P < 0.01), and also increased the synthesis of Triglyceride (TG) and Cholesterol (TC) in granulosa cells (P < 0.05), whereas NPC2 overexpression led to a marked reduction in the expression of these indicators of lipid metabolism (P < 0.01). Furthermore, NPC2 knockdown significantly inhibited the production of progesterone (P4) (P < 0.01) and estradiol (E2) (P < 0.05), along with the expression of STAR, CYP17A1 steroidogenesis-related genes in granulosa cells (P < 0.05). Conversely, NPC2 overexpression enhanced P4 and E2 synthesis and upregulated the expression of genes associated with steroid hormone biosynthesis (P < 0.05). Taken together, these findings indicate that NPC2 suppresses lipid accumulation while promoting steroid hormone production in chicken granulosa cells, which highlights its potential regulatory role in ovarian function.